Stemming the tide of plagiarism in thesis writing in Nigerian library schools through policy and competence: implications for quality assurance (2016)
Plagiarism is an act that is capable of jeopardizing quality assurance in library schools. This academic crime if left unchecked can call into question the reputation and value of degrees conferred on students in Nigerian library schools. Even though technology has been employed to combat plagiarism in some library schools through the use of detection software like Turnilin, Copycatch, Plagscan etc., this unwholesome act seems to continue unhindered. This reveals the need to adopt a holistic strategy to combat this menace, especially as it applies to thesis writing in library schools. The strategy includes the use of effective quality assurance methods. This paper therefore discusses the role of plagiarism policy formulation and implementation, as well as the development of competencies in library and information science (LIS) students as quality assurance methods that can reduce the rate of plagiarism in Nigerian library schools. The content of such policy was explained and the various ways of building LIS students’ competencies were sufficiently discussed. Finally, the paper recommended the formulation and/or strict application of institutional policy on plagiarism and the development of students ’ competencies in order to stem the tide of plagiarism and enhance quality assurance in LIS postgraduate education in Nigeria.